Turn to turn fault analysis of three phase PMSG for different rotor air gap - Parashar S.; Srivastava R.K. (My University, 2025)
This paper presents an approach to study the performance of Three phase Permanent Magnet Synchronous Generator for different rotor air gap during inter-turn fault. Winding Function Theory has been used for study of abnormal behavior in the machine during winding fault. Winding Function Theory(WFT) provides an easier way to model winding inductances of machine under healthy and unhealthy conditions. Mathematical modeling has been done to get the expressions relating effect of air gap to various performance parameters of generator during fault. Results obtained by mathematical modeling have been thoroughly studied and validated using experimental results. © 2015 IEEE.